Antiretroviral resistance mutations in human immunodeficiency virus type 1 infected patients enrolled in genotype testing at the Central Public Health Laboratory, São Paulo, Brazil: preliminary results - Rodrigues, Rosangela; Vazquez, Carla Maria Pasquareli; Colares, Jeova Keny; Custodio, Renata Marconi; Bonásser Filho, Francisco; Souza, Lenice do Rosario de [UNESP]; Gianna, Maria Clara; Marques, Cristiano Corrêa de Azevedo; Brígido, Luís Fernando de Macedo [UNESP] (Instituto Oswaldo Cruz, Ministério da Saúde, 2005)
Antiretroviral resistance mutations (ARM) are one of the major obstacles for pharmacological human immunodeficiency virus (HIV) suppression. Plasma HIV-1 RNA from 306 patients on antiretroviral therapy with virological failure was analyzed, most of them (60%) exposed to three or more regimens, and 28% of them have started therapy before 1997. The most common regimens in use at the time of genotype testing were AZT/3TC/nelfinavir, 3TC/D4T/nelfinavir and AZT/3TC/efavirenz. The majority of ARM occurred at protease (PR) gene at residue L90 (41%) and V82 (25%); at reverse transcriptase (RT) gene, mutations at residue M184 (V/I) were observed in 64%. One or more thymidine analogue mutations were detected in 73%. The number of ARM at PR gene increased from a mean of four mutations per patient who showed virological failure at the first ARV regimens to six mutations per patient exposed to six or more regimens; similar trend in RT was also observed. No differences in ARM at principal codon to the three drug classes for HIV-1 clades B or F were observed, but some polymorphisms in secondary codons showed significant differences. Strategies to improve the cost effectiveness of drug therapy and to optimize the sequencing and the rescue therapy are the major health priorities.
Keywords: human immunodeficiency virus; diversity; antiretroviral resistance; Brazil